Harmonic scalpel thyroidectomy versus conventional haemostasis thyroidectomy - Haq, Ajaz U.; Mahmood, Tariq; Kumari, Sheetal; Afzal, Aneesa (International Surgery Journal, 2021)
Background: As there is paucity of data on harmonic scalpel thyroidectomy from Jammu and Kashmir belt. So, we conducted this study to bridge this gap and also to create awareness about the use of harmonic scalpel. Thyroidectomy has become one of the most common and frequent surgery. Hemostasis in thyroid surgery is of utmost importance for a successful surgery. Our aim was to compare operative factors, postoperative outcomes of thyroidectomy using the Harmonic Scalpel (HS) and Conventional Haemostasis (CH). Methods: In this randomized control trial study, 100 patients who underwent thyroidectomy were enrolled and randomly divided in two groups- HS group and CH group. The inclusion criteria were age>18years, acceptance to participate in the study (signed informed consent form) and scheduled total thyroidectomy. The groups were compared with regards to age, gender, operative time, post-operative drainage volume, postoperative pain, and hospital stay. Results: The mean age in years was 39.8 years for HS group and 43.8 years for CH group with female preponderance. There was a significant difference with regards to operative time, post-operative drainage volume, postoperative pain, and hospital stay (p<0.001). Harmonic Scalpel shortens the operative time. And there was less post-operative drainage volume and postoperative pain in HS group. Hospital stay was also less as compared to CH group. Conclusions: HS is superior then CH thyroidectomy and is considered as a safe and better tool in thyroidectomy.